HIERARCHICAL AND ITERATIVE METHOD OF CHOOSING THE PARAMETERS OF THE POWER CHARACTERISTICS AND DESIGN SOLUTIONS OF SUSPENSION BOGIE FREIGHT WAGONS, INTEGRATED INTO A COMPREHENSIVE DESIGN METHODOLOGY UNDERCARRIAGE PARTS - Orlova, A. M. (Science and Transport Progress, 2008)
In the article a generalized method of analysis of dynamic behavior, choice of parameters and designs of freight wagon bogies based upon the hierarchy of mathematical models, which describe the vehicle motion with different degree of sophistication, is suggested. The method application is shown on the example of three-piece bogie.